Analysis of the associations of the T-786C and Glu298Asp polymorphisms of the eNOS gene as risk factors in the rupture of intracranial aneurysms - Lopes, Marta Marques de Carvalho; Rojas, Hugo Alberto; Polizzi, Luiza Franklin; Magalhaes, Kenia Cristina S. F.; Sandrim, Valeria Cristina [UNESP]; Dellaretti, Marcos; Rubatino, Fernando Victor Martins; Simoes, Renata Toscano (Elsevier B.V., 2022)
The mechanisms involved in aneurysmal etiology are complex and only partially understood. Genetic risk factors have already been related to the process of aneurysm rupture. Among the genetic factors, the T-786C and Glu298Asp polymorphisms of the eNOS gene have great clinical relevance, as they can affect the bioavailability of nitric oxide for the cerebrovascular system. Objective: To evaluate the relationship between eNOS T-786C and Glu298Asp polymorphisms and the aneurysm pathogenesis of patients seen in the Neurosurgery Department of Santa Casa de Belo Horizonte, as well as to compare them with sociodemographic characteristics and risk factors. Methods: A total of 211 whole blood samples were collected from patients with cerebral aneurysms, 160 with ruptured aneurysms, 51 with unruptured aneurysms and 215 controls. After DNA extraction, genotyping was performed using the PCR-RFLP technique. Allele and genotype frequencies were obtained using the GENEPOP 4.2 software, and statistical analysis was performed using the GraphPad Prism 5.0 program and RStudio version 1.4. Results: Age, female sex, smoking and small diameter of the aneurysms were associated with aneurysm development and rupture in the study population. The CC genotype of the T-786C polymorphism was associated with unruptured aneurysms with a diameter >12 mm. Conclusion: Age, female sex and smoking were associated with rupture. This study revealed that the CC mutant genotype of the eNOS gene T-786C polymorphism was associated with unruptured intracranial aneurysms larger than 12 mm in our study population, revealing a new association.
Keywords: Cerebral aneurysms; Risk factors; Polymorphisms of the eNOS gene